Spatio-temporal variation of food guilds of phytophagous beetles’ (Coleoptera: Scarabaeidae) in the Colombian Caribbean - García-Atencia, Sandy; Amat-García, Germán (Revista Colombiana de Entomología, 2021)
In the Colombian Caribbean, in addition to landscape modifications due to changes in land use, marked periods of drought and rainfall affect the survival of organisms. These changes modulate the supply of resources for scarabs with broad feeading habits. The spatio-temporal variation of scarab beetle guilds in a fragment of Tropical Dry Forest (Bs-T) and a surrounding crop was evaluated in six samplings; in each zone, four light traps were placed between18:00 to 6:00 and temperature, humidity and precipitation variables were measured. In the forest 5,184 individuals distribuited in 19 species were collected, and in the crop 1,919 individuals belonging to 16 species of subfamilies Dynastinae, Melolonthinae and Rutelinae. The phytophagous scarab beetles from forest and crop were represented by four guilds: Rhizo-Phylophagous (RP), Sapro-Caulophagous (SC), Sapro-Meliphagous(SM) and Xilo-Philo- phagous (XP); the predominant guild corresponded to the RP with ten species. In forest and crop, the dominant guild was RF with ten species, and the least number of species and guilds were collected in March, July and August, while May presented the highest diversity of species and guilds. The above coincides with the increase of precipitation, that showed positive correlation with richness and abundance in forest (p = 0.77, both cases) and crop (p = 0.84 and p = 0.66, respectively) during May. The guilds of phytophagous fluctuated in composition, richness, and abundance mainly in response to climatic seasonality, rather than the characteristics of each of the area.